PORTRAIT OF DIVERSITY AND RELIGIOUS HARMONY IN AMBON STATE CHRISTIAN INSTITUTE - Sudirman Simanihuruk; Jenri Ambarita; Johanes Waldes Hasugian (Adisam Publisher, 2023)
The State Christian Institute of Ambon is a Christian religious higher education institution with lecturers, employees, and students of various faiths. Religious differences are often a point of conflict, but there has never been a conflict within the Institut Agama Kristen Negeri Ambon (IAKN Ambon) environment, despite different religious beliefs. Therefore, the purpose of this research is to know the portrait of religious diversity, the understanding of students, staff, and lecturers about religious harmony, the values of religious harmony, and the efforts made to build religious harmony at IAKN Ambon. This research uses a qualitative method for data collection, such as in interviews, participant observation, and document reviews, which would then be analyzed using qualitative descriptive techniques. This study's informants included Christian, Muslim, and Catholic lecturers, staff, and students. According to the results, there were three religious communities in IAKN Ambon: Islam, Christianity, and Catholicism. Relations among religious communities are excellent. This harmony can be seen in mutual respect, freedom of worship, and cooperation. This harmony has been built through several efforts, such as 1) providing understanding and awareness of the importance of harmony; 2) providing freedom of worship; 3) providing worship facilities; and 4) creating a common space.